Absence of Early Neuronal Death in the Olivocochlear System Following Acoustic Overstimulation. Issue 1 (30th October 2015) - Reuss, Stefan; Closhen, Christina; Riemann, Randolf; Jaumann, Mirko; Knipper, Marlies; Rüttiger, Lukas; Wolpert, Stephan
ABSTRACT: This study was conducted to examine possible effects of noise trauma on olivocochlear (OC) neurons. Anesthetized rats were exposed to a continuous 10 kHz pure tone at 120 dB sound pressure level for 2 hrs. The effects of treatment were verified by recordings of auditory brainstem response and distortion product otoacoustic emission. Three or 8 days after acoustic trauma, rats received unilateral injections of an aqueous solution of the retrograde neuronal tracer Fluorogold (FG) into the scala tympani to identify OC neurons (OCN). Five days after FG injection, brains were perfusion‐fixed, and brainstem sections were cut and analyzed with respect to FG‐labeled neurons. We found that, in both groups, numbers of OCN were similar to that of controls. The incubation of a second set of sections with antibodies against choline‐acetyltransferase (the enzyme responsible for acetylcholine synthesis) showed the cholinergic neurons of the brainstem, however, without suggesting differences between groups. Our study, the first to investigate noise trauma effects on identified OCN, revealed that no visible alterations occurred in 2 weeks following trauma, neither in identified OCN nor in choline‐acetyltransferase‐immunofluorescence. At this time, auditory brainstem response and distortion product otoacoustic emission measurements showed severe signs of hearing loss. The mechanisms leading to hearing loss upon noise trauma apparently do not involve degeneration of OCN. Anat Rec, 299:103–110, 2016. © 2015 Wiley Periodicals, Inc.